Lead isotopic systematics of massive sulphide deposits in the Urals: Applications for geodynamic setting and metal sources - Tessalina, Svetlana; Herrington, R.; Taylor, R.; Sundblad, K.; Maslennikov, V.; Orgeval, J. (Elsevier, 2016)
Lead isotopic compositions of 61 samples (55 galena, one cerussite [PbCO3] and five whole ore samples) from 16 Volcanic Hosted Massive Sulphide (VHMS) deposits in the Urals Orogeny show an isotopic range between 17.437 and 18.111 for 206Pb/204Pb; 15.484 and 15.630 for 207Pb/204Pb and 37.201 and 38.027 for 208Pb/204Pb. Lead isotopic data from VHMS deposits display a systematic increase in ratios across the Urals paleo-island arc zone, with the fore-arc having the least radiogenic lead compositions and the back-arc having the most radiogenic lead. The back arc lead model ages according to Stacey–Kramers model are close to the biostratigraphic ages of the ore-hosting volcano-sedimentary rocks (ca. 400 Ma). In contrast, less radiogenic lead from the fore-arc gives Neoproterozoic (~ 700 Ma) to Cambrian (480 Ma) lead model ages with low two-stage model μ values of 8.8 (parameter μ = 238U/204Pb reflects the averaged U/Pb ratio in the lead source), progressively increasing stratigraphically upwards to 9.4 in the cross-section of the ore-hosting Baymak–Buribai Formation. The range of age-corrected uranogenic lead isotopic ratios of the volcanic and sedimentary host rocks is also quite large: 206Pb/204Pb = 17.25–17.96; 207Pb/204Pb = 15.48–15.56, and generally matches the ores, with the exception of felsic volcanics and plagiogranite from the Karamalytash Formation being less radiogenic compare to the basaltic part of the cross-section, which would potentially imply a different source for the generation of felsic volcanics.This may be represented by older Neoproterozoic oceanic crust, as indicated by multiple Neoproterozoic ages of mafic–ultramafic massifs across the Urals. The relics of these massifs have been attributed by some workers to belong to the earlier Neoproterozoic stage of pre-Uralian ocean development. Alternative sources of lead may be Archean continental crust fragments/sediments sourced from the adjacent East-European continent, or Proterozoic sediments accumulated near the adjacent continent and presently outcropping near the western edge of Urals (Bashkirian anticlinorium). The contribution of Archean rocks/sediments to the Urals volcanic rock formation is estimated to be less than 0.1% based on Pb–Nd mixing models. The most radiogenic lead found in VHMS deposits and volcanics in the Main Uralian Fault suture zone, rifted-arc and back-arc settings, show similar isotopic compositions to those of the local Ordovician MORBs, derived from highly depleted mantle metasomatized during dehydrational partial melting of subducted slab and oceanic sediments. The metasomatism is expressed as high Δ 207Pb/204Pb values relative to the average for depleted mantle in the Northern hemisphere, and occurred during the subduction of oceanic crust and sediments under the depleted mantle wedge. A seemingly much younger episode of lead deposition with Permian lead model ages (ca. 260–280 Ma) was recorded in the hanging wall of two massive sulphide deposits.